The Making and Meaning of Relationships in Sri Lanka An Ethnography on University Students in Colombo - Sirisena, Mihirini (Culture, Mind, and Society, 2018)
This book proposes that romantic relationships-filtered through various socio-cultural sieves-can lead to the development of affective kin bonds, which underlie our sense of personhood and belonging. Sirisena argues that the process resembles an attempt to make strangers into kin, and that sort of affective relating is a form of self-conscious relationality, in which the inhabitants reflect on their individual and collective needs, as well as their expectations and dreams in the future of their relationships. University students' romantic relationships, which they gloss as 'serious,' appear to be processual and non-linear, and are considered to be stabilising forces which are pitched against the inherent uncertainty in young people's lives.